Understanding the biomimetic properties of gallium in Pseudomonas aeruginosa: an XAS and XPS study. Issue 21 (19th May 2017) - Porcaro, F.; Bonchi, C.; Ugolini, A.; Frangipani, E.; Polzonetti, G.; Visca, P.; Meneghini, C.; Battocchio, C.
Abstract : The structural and electronic investigation of the biomimetic properties of gallium ions by means of synchrotron techniques in the Ga/Fe–pyochelin complex. Abstract : Pyochelin (PCH) is a siderophore (extracellular chelator) produced by the pathogenic bacterium Pseudomonas aeruginosa (PAO). PCH is implicated in iron (Fe 3+ ) transport to PAO, and is crucial for its metabolism and pathogenicity. Due to the chemical similarity with Fe 3+, gallium (Ga 3+ ) interferes with vital iron-dependent processes in bacterial cells, thereby opening new perspectives for the design of specific metal-based antibacterial drugs. However, the structural basis for the Fe 3+ -mimetic properties of Ga 3+ complexed with the PCH siderophore is still lacking. A precise knowledge of the coordination chemistry at the metal site is one of the topmost issues in the production of novel biomimetic metal-based drugs. Elucidation of this issue by means of a deep structural spectroscopic investigation could lead to an improved interference with, or a specific inhibition of, relevant biological pathways. For this reason, we applied Synchrotron Radiation induced X-ray Photoelectron Spectroscopy (SR-XPS) and X-ray Absorption Spectroscopy (XAS) to probe the electronic nature and coordination chemistry of Fe 3+ and Ga 3+ coordinative sites in PCH metal complexes. Combined XAFS and SR-XPS studies allow us to demonstrate that both Fe and Ga have the same valence state in Fe–PCH and Ga–PCH, and have the same octahedral coordination geometry. Moreover, a similar next neighbour distribution for Fe and Ga, resulting from the EXAFS data analysis, strongly supports similar coordination chemistry at the origin of the biomimetic behaviour of Ga.